Analysis of the Linguistic Personality as a Subject of Psycholinguistic Research: Dynamics of Development and Forecasts for the Future - Svitlana Romanchuk; Olena Kuzmenko; Marharyta Berezhna; Anatolii Vysoskyi; Tetiana Nikolaieva (Forum for Linguistic Studies, 2024)
This study explores the psycholinguistic aspects of speech as a cognitive process, integrating linguistic, communicative, and socio-cultural elements. The research addresses the novelty of examining how segmentation, comprehension, storage, and information integration contribute to enhancing communication skills and developing speech abilities. Additionally, it introduces a fresh perspective on psycholinguistic discourse analysis, highlighting the importance of collaboration between disciplines such as psycholinguistics, sociolinguistics, and artificial intelligence. The key findings indicate that linguistic markers (LM) and discourse markers (DM) are crucial in processing speech and interaction. The study also emphasizes the multimodal aspects of communication – written language, gestures, gazes, and postures – as essential factors in speech perception. The results demonstrate that revising the epistemological framework for understanding discourse semantics is necessary for advancing the field. By proposing new approaches, the study lays the groundwork for future interdisciplinary research and contributes to advancing knowledge of psycholinguistics and communication studies. This study emphasizes the interdisciplinary integration of psycholinguistics and communication studies, focusing on the role of linguistic and discourse markers in cognitive and social interactions. The findings advocate for enhancing educational approaches by integrating psycholinguistic insights to support language development. This research contributes to a deeper understanding of language processing dynamics by addressing challenges in multimodal communication and cognitive load management. It paves the way for innovative applications in artificial intelligence and sociolinguistics.